Analisis Proses Bisnis Pada Toko Buku Galuh Menggunakan Business Process Improvement Framework - Adeyaksa Galuh Waluyo; Ismiarta Aknuranda; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Toko Buku Galuh is a company engaged in retail business. Toko Buku Galuh has stood since 1998, and has grown to the present. Vision Galuh Bookstore to be at the forefront of the retail business of books in Sidoarjo. Problems arise as the company grows larger that there is no written business process that becomes the benchmark in running the business, so that the decisions made can be changed based on the conditions leading to less effective and efficient business processes. For that required analysis of business processes using Business Process Improvement (BPI) Framework. The first phase of editing Toko Buku Galuh business process uses Business Process Model and Notation (BPMN), the second phase performs Process Validation, Time Validation and Resource Validation on business processes. Then determine the streamlining used to improve the effectiveness and efficiency of business processes. From the results of the proposed analysis obtained increased time on sale transactions 64.37%, buyer transactions 77,9%, price tagging 30%, and edit items data 25.9%.